1999
DOI: 10.1097/00002030-199907090-00017
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviours, perception of risk of HIV infection, and factors associated with attending HIV post-test counselling in Ethiopia

Abstract: Study participants reported high-risk sexual behaviours, yet had a low perception of individual risk. Men attended for PTC because of their knowledge of HIV infection, their past sexual history or their current health status. Women attended for PTC because of their plans for the future, marriage and/or children, rather than their past sexual exposure. Only in cases of rape were they willing to learn of their HIV status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…Although the majority of the young people had received life skills or life orientation education and had higher levels of education, they still engaged in risky sexual behaviour, and did not use the skills and knowledge gained to prevent exposure to HIV and STI. There were similarities with the results of a study conducted by SahluKassa, Agonafer, Tsegaye, De Wit, Gebremariam et al (1999Gebremariam et al ( :1271, which showed that men who had good knowledge of HIV and its transmission still engaged in risky sexual behaviour, despite the knowledge and skills gained.…”
Section: Resultssupporting
confidence: 82%
“…Although the majority of the young people had received life skills or life orientation education and had higher levels of education, they still engaged in risky sexual behaviour, and did not use the skills and knowledge gained to prevent exposure to HIV and STI. There were similarities with the results of a study conducted by SahluKassa, Agonafer, Tsegaye, De Wit, Gebremariam et al (1999Gebremariam et al ( :1271, which showed that men who had good knowledge of HIV and its transmission still engaged in risky sexual behaviour, despite the knowledge and skills gained.…”
Section: Resultssupporting
confidence: 82%
“…11 In Ethiopia, a cohort study of factory workers with a high prevalence of HIV reported high-risk sexual behavior and low condom use, even though the majority mentioned condom use as the best way to prevent HIV. 12 A study using 1998 Kenyan DHS data reported that the odds of having risky sexual behavior were more than tripled among men and women who perceived their risk of HIV/AIDS as high, and found no association between knowledge of HIV transmission and sexual behavior. 13 The relationship between perception of risk and sexual behavior is complex and poorly understood.…”
mentioning
confidence: 99%
“…The cohort was formed to study the natural history of HIV-1 infection in Ethiopia and has been described elsewhere (34,35). Blood was collected using EDTA anticoagulant as required for routine viral load determination using the NucliSENS HIV-1 QT assay (bioMérieux, Boxtel, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%